Unsteady magnetohydrodynamics flow of a micropolar fluid with heat and mass transfer - Mangi, Aurangzaib (2013)
The unsteady boundary layer flow has become of great interest in the field of fluid mechanics including the area of convective double diffusion. This is due to the complexity of the problem by including extra independent time variable, especially in the study of magnetohydrodynamic flow immersed in a micropolar fluid. In this thesis, the unsteady two-dimensional laminar boundary layer and mixed convection stagnation point flow towards a stretching or shrinking sheet immersed in magnetohydrodynamic micropolar fluid are considered. Specific problems are considered with different effects such as Soret and Dufour effects, thermophoresis effect and slip effect. Along with these effects, the micropolar parameter, the magnetic parameter and the suction or injection parameter are also considered. The governing non-linear equations are transformed into a system of differential equations by using appropriate non-dimensional variables which are then solved numerically using an implicit finite difference scheme. Numerical results for the skin friction, the Nusselt number and the Sherwood number as well as the velocity, microrotation, temperature and concentration profiles for different physical parameters are presented graphically and in tabular form. The results obtained show that there is a smooth transition from small time solution to large time solution. It is also found that with an increase of Soret and Dufour numbers, the momentum boundary layer thickness increases whereas the microrotation boundary layer thickness decreases for assisting flow while a reverse trend is observed for opposing flow. The thermal and concentration boundary layer thicknesses increase in both cases. By increasing the values of the slip parameter, all the boundary layer thicknesses decrease. In addition, by increasing the values of thermophoresis, the concentration boundary layer thickness decreases.